PENGGUNAAN MEDIA BERBASIS TEKNOLOGI DALAM MEMBANGUN LITERASI DIGITAL ANAK USIA DINI - Rahman Wahid; Siti Purhasanah; Neneng Jessi Asrina (Jurnal El-Audi, 2023)
The utilization of technology-based learning media is something that can no longer be avoided in the learning process by teachers. In the era of increasingly massive technological developments, teachers should be able to provide experience to children so that they can use technology wisely. In line with that, in the context of early childhood education, the introduction to technology is an important thing to do considering that at this time technology is no longer only used by adults, but early childhood has also been faced with a life that is closely related to technology. Thus, it is important for teachers to instill technological and digital literacy skills to early childhood, so that they can then become wise people in using technology.